2017
DOI: 10.1097/rli.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Critical Questions Regarding Gadolinium Deposition in the Brain and Body After Injections of the Gadolinium-Based Contrast Agents, Safety, and Clinical Recommendations in Consideration of the EMA's Pharmacovigilance and Risk Assessment Committee Recommendation for Suspension of the Marketing Authorizations for 4 Linear Agents

Abstract: For magnetic resonance, the established class of intravenous contrast media is the gadolinium-based contrast agents. In the 3 decades since initial approval, these have proven in general to be very safe for human administration. However, in 2006, a devastating late adverse reaction to administration of the less stable gadolinium-based contrast agents was identified, nephrogenic systemic fibrosis. The result of actions taken by the European Medicines Agency and the US Food and Drug Administration, stratifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 51 publications
(62 reference statements)
2
118
1
1
Order By: Relevance
“…Although the biases were substantial, we found that our findings (in all but one incongruent lesion Gd‐EOB‐DTPA was finally correct) are still significant enough to change our policy to the preferential use of Gd‐EOB‐DTPA. Even though a prospective study using both contrast agents in the same patients would help confirm our current findings, we would have considerable ethical difficulty with this approach in light of the current discussion concerning linear contrast agents and deposition in the brain …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although the biases were substantial, we found that our findings (in all but one incongruent lesion Gd‐EOB‐DTPA was finally correct) are still significant enough to change our policy to the preferential use of Gd‐EOB‐DTPA. Even though a prospective study using both contrast agents in the same patients would help confirm our current findings, we would have considerable ethical difficulty with this approach in light of the current discussion concerning linear contrast agents and deposition in the brain …”
Section: Discussionmentioning
confidence: 69%
“…One might argue that, besides HBP, imaging diagnosis of these benign entities is generally based on a combination of all imaging parameters. In most circumstances, final diagnoses can be reached based only on typical findings . Although the aim of our study was to specifically clarify the utility of HBP in establishing a final diagnosis, future studies could address the question of the relative importance of HBP compared with other imaging parameters in typical cases.…”
Section: Discussionmentioning
confidence: 99%
“…No adverse clinical or pathological consequences of Gd deposition in the brain have thus far been confirmed . However, precautionary recommendations have been made in the use of linear GBCA by professional organizations and the Food and Drug Administration . At a recent international workshop of experts held at the National Institutes of Health, the current state of knowledge regarding Gd deposition from GBCA was reviewed and the importance of identifying populations of patients who may be vulnerable to deposition of Gd from GBCA was acknowledged …”
Section: Discussionmentioning
confidence: 99%
“…The significance of this concern has been challenged by the broad radiology community and lack of current clinical evidence of deleterious effects . However, linear GBCA have been largely withdrawn in Europe in favor of macrocyclic agents, which do not undergo dechelation . The Food and Drug Administration has issued warnings regarding the use of GBCA in potentially vulnerable populations, such as children and those with blood–brain barrier (BBB) disruption .…”
Section: Introductionmentioning
confidence: 99%
“…Breast MRI is based on the dynamic contrast enhanced (DCE) technique with gadolinium injection in order to differentiate neoangiogenesis in malignant lesions from benign lesions . However, recent studies have questioned the use of external contrast agent, including its deposition in the brain or its adverse reaction in patients with renal failure . A screening of high‐risk women has to be performed by breast MR every year and the long‐term impact of these deposits on cognitive functions is still unknown.…”
Section: Introductionmentioning
confidence: 99%